Perceptions of the CanMEDS Competencies of Faculty and Students in Different Curriculum Systems of a Medical School in China - Li P; Jiang F; Yin L; Chen YQ; Shao L; Li Y; Gao YJ; Lu MH (Advances in Medical Education and Practice, 2022)
Pingping Li,1 Fan Jiang,2 Lei Yin,3 Yi Qi Chen,4 Li Shao,5 Yi Li,6 Yi Jin Gao,7 Mei Hua Lu1 1Department of Medical Teaching, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Department of Developmental and Behavior Pediatrics, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 3Department of Nephrology, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 4School of Pediatrics, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 5Office of Educational Administration, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 6School of Clinical Medicine, Renji Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 7Department of Hematology/Oncology, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of ChinaCorrespondence: Mei Hua Lu; Yi Jin Gao, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China, Tel +86 021 38626190, Email lumeihua@scmc.com.cn; gaoyijin@gmail.comIntroduction: The Ottawa-Shanghai Joint School of Medicine (OSJSM) has adopted the uOttawa’s undergraduate medical education (UGME) program vertically integrated (VI) curriculum.However, limited information is available regarding whether the VI and non-VI curricula foster different perspectives on necessary competencies.Methods: This study included 167 undergraduate medical students and 142 faculty members from different curricula at the Shanghai Jiao Tong University School of Medicine. Participants completed a questionnaire, rating the importance of competencies relating to the seven CanMEDS roles.Results: The cognitive level regarding the competencies required to be a successful clinician was significantly higher among participants from VI versus non-VI curricula. All participants gave the highest ratings to the Medical Expert and Professional roles, and rated the Health Advocate role as least important. Competency ratings did not significantly differ between students from VI versus non-VI curricula. Ratings between VI and non-VI faculty showed only one significant difference, namely the competence of“Constantly update clinical knowledge and professional skills” was ranked significantly higher by faculty of non-VI curricula. In the top rated 10 competencies, the Communicator role was considered more important by participants from VI versus non-VI curricula.Conclusion: The cognitive level regarding the competencies was related to the curriculum system. The Communicator role seemed to be paid more attention in VI curricula, however, other competencies was not demonstrated to be related to the curriculum system.Keywords: competency, vertically integrated curriculum, medical education